Endoplasmic reticulum stress in the development of multiple myeloma and drug resistance - Nikesitch, Nicholas (Clin Transl Immunology, 2018)
Multiple myeloma (MM) is a haematological malignancy of mature antibody‐secreting plasma cells. Currently, MM is incurable, but advances in drug treatments have increased patient lifespan. One of the characteristics of MM is the excessive production of monoclonal immunoglobulin (also referred to as paraprotein). This high level of protein production induces endoplasmic reticulum (ER) stress, and proteasomal degradation of the paraprotein is required to avoid ER stress‐induced cell death. Consequently, proteasomal inhibitors such as bortezomib have been particularly effective therapies. Unfortunately development of resistance to bortezomib is common. In this review, we address how control of endoplasmic reticulum stress is important in the development of MM and how the unfolded protein response and its associated stress response pathways are involved in the development of bortezomib resistance.